2021
DOI: 10.26786/1920-7603(2020)601
|View full text |Cite
|
Sign up to set email alerts
|

Pollinator effectiveness in the mixed-pollination system of a Neotropical Proteaceae, <i>Oreocallis grandiflora</i>

Abstract: In pollination systems with a diverse community of floral visitors, qualitative and quantitative variations in pollination effectiveness can lead to a system in which higher effectiveness results from the synergetic contribution of multiple pollinators. By employing a series of field and laboratory experiments in the south Andes of Ecuador, we compared the effectiveness of hummingbirds and nocturnal mammals visiting Oreocallis grandiflora, an Andean member of the Proteaceae. Pollinator effectiveness was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
(70 reference statements)
0
2
0
Order By: Relevance
“… 18 , 24 Small bees had the highest abundance based on their visitation rate, 32 and therefore may be the most effective visitors contributing to pollination. 33 Small bees were the most commonly documented visitor, making up 59% of all recorded interactions. Since visitation rates can serve as a measure of abundance, 32 we can conclude that small bees are the most abundant pollinators of N. rustica.…”
Section: Discussionmentioning
confidence: 99%
“… 18 , 24 Small bees had the highest abundance based on their visitation rate, 32 and therefore may be the most effective visitors contributing to pollination. 33 Small bees were the most commonly documented visitor, making up 59% of all recorded interactions. Since visitation rates can serve as a measure of abundance, 32 we can conclude that small bees are the most abundant pollinators of N. rustica.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, individual Cape sugarbirds showed high levels of flower constancy (Schmid et al, 2016) which should increase conspecific pollen transfer (Chittka et al, 1999). Although studies have shown that visitation frequencies and pollination quality may be unrelated in hummingbirds (Cárdenas-Calle et al, 2021;Watts et al, 2012), other studies from the Fynbos biome strongly suggest that birds are indeed reliable pollinators of proteas. The compact and protandrous protea florets mainly burst open by the strong force of probing bird pollinators (Collins & Rebelo, 1987), which explains why experimental studies found that birds are better pollinators than insects for many Protea species (Hargreaves et al, 2004;Schmid et al, 2015a).…”
Section: Pollinator Specialization and Potential Pollination Servicesmentioning
confidence: 99%
“…Mutualist and antagonist floral effectiveness can thus be used as a proxy to estimate the variation in reproductive success among plants within populations depending on the quantity and the impact of visitations made by both pollinators and antagonists. Several studies have demonstrated that visitors with a high quantitative performance (e.g., insects) contrast with those of high qualitative performance (e.g., birds) in pollination effectiveness of plant species visited by multiple taxonomic and functional groups (Cárdenas‐Calle et al., 2020; Hervías‐Parejo & Traveset, 2018; Rodríguez‐Rodríguez et al., 2013). Therefore, determining the effectiveness of flower visitation among different types of flower visitors and individual plants is suitable to identify the most efficient pollinators against the most detrimental floral antagonists.…”
Section: Introductionmentioning
confidence: 99%